CATCH COMPOSITION OF POT WITH DIFFERENT BAIT AT BATANG KUMU WATERS ROKAN HILIR REGENCY - Nopriyanti; Iskandar, Mokhamad Dahri; Mawardi, Wazir; Komarudin, Didin; Baskoro, Mulyono S. (Jurnal Penelitian Perikanan Laut (Albacore), 2025)
Pot is the dominant fishing gear for capturing fish at Batang Kumu River. Fishermen operated pot for targeting redtail catfish without any bait. At this research pot pot was attached with trash fishes, palm oil to increase catch of pot in Batang Kumu river. The purpose of this experiment to investigate catch composition of pot and number of fish catch using different bait. This research used 3 different treatments i.e pot with trash fishes bait, pot with palm oil bait and pot without bait as control. Each treatment used 8 pots. Total pots used at this research were 24 pots. Total catch number and weight was analyzed by Kruskall Wallis test while catch homogeneity was analyzed by Shannon Wiener Index. Result of experiment indicated that dominant catch was redtail catfish, 57% of total catch. Kruskal Wallis test indicated that number of catch and weight of total siginificantly different among different bait type. The results of the analysis of the diversity of catches showed that the traps using trash bait had the lowest Diversity Index, Key words: Bait, Batang Kumu River, pot, Shannon Wiener